2012
DOI: 10.3851/imp2010
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Drug Resistance and Loss of Therapeutic Options Precede Commonly Used Criteria for Treatment Failure in HIV-1 Subtype-C-Infected Patients

Abstract: Rapid accumulation of drug resistance occurred when ART was continued despite virological failure. Treatment options were lost, even when WHO-defined failure criteria were not met. This study calls for wider access to virological monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 27 publications
5
40
0
Order By: Relevance
“…Based on immunological criteria in this study, 30% of the patients would have been classified as not failing, and therefore not switched to second line. Failure to switch a failing regimen has been shown to result into accumulation of mutations that will limit future treatment options [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Based on immunological criteria in this study, 30% of the patients would have been classified as not failing, and therefore not switched to second line. Failure to switch a failing regimen has been shown to result into accumulation of mutations that will limit future treatment options [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of VL in patients in sub-Saharan African ART programs (6) found similar prevalences of virological failure (median, 14% at a 1,000-copies/ml cut point and 10% at a 5,000-copies/ml cut point) as those found in our study. It has been shown, however, that drug resistance can develop in patients with a sustained VL of Ͼ1,000 copies/ml (25). Although current WHO guidelines recommend using a threshold of 1,000 copies/ml to define virological failure, they recommend the use of a cut point of 5,000 copies/ml for programs testing VL in DBS samples (1).…”
Section: Discussionmentioning
confidence: 99%
“…Informed therapy switching can prevent unnecessary treatment switching (4) to more expensive and less accessible second-line therapies. Moreover, early detection of VF using the VFA can prevent extended exposure to a failing regimen and possible accumulation of drug resistance mutations that may confer cross-resistance to other drugs or drug classes (8). Using the VFA for early detection of treatment failure could also prevent HIV-1 transmission (18).…”
Section: Discussionmentioning
confidence: 99%
“…Timely detection of VF by viral load (VL) testing, which is routine in industrialized countries (7), is necessary to prevent accumulation of HIV drug resistance (8) or to identify poor adherence to the treatment. However, in RLS, high costs and technical complexity limit VL monitoring, and treatment failure is determined primarily by clinical monitoring for stage three and four AIDS-defining illnesses and, if available, immunological monitoring using CD4 counts (6).…”
mentioning
confidence: 99%